2021
DOI: 10.3389/fgene.2021.656571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PCBP1 as a Novel Modulator of Mammalian Circadian Clock

Abstract: The circadian clock governs our daily cycle of behavior and physiology. Previous studies have identified a handful of core clock components and hundreds of circadian modifiers. Here, we report the discovery that poly(C)-binding protein 1 (PCBP1), displaying a circadian expression pattern, was a novel circadian clock regulator. We found that knocking down PCBP1 resulted in period shortening in human U2OS cells, and that manipulations of PCBP1 expression altered the activity of CLOCK/BMAL1 in an E-box-based repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…may also be closely associated with PD, although the exact mechanism remains unclear (Wu et al, 2021). However, to date, no animal experiments have been conducted to investigate the specific mechanism of PCBP1 in regulating the process of PD models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…may also be closely associated with PD, although the exact mechanism remains unclear (Wu et al, 2021). However, to date, no animal experiments have been conducted to investigate the specific mechanism of PCBP1 in regulating the process of PD models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, abnormal nuclear distribution of PCBP1 has been implicated in the pathogenesis of Huntington's disease (HD), suggesting that RBPs, including PCBP1, may play a role in the pathophysiological processes underlying neurodegenerative conditions (Geuens et al., 2017 ). Given the shared pathophysiology between PD and HD, PCBP1 may also be closely associated with PD, although the exact mechanism remains unclear (Wu et al., 2021 ). However, to date, no animal experiments have been conducted to investigate the specific mechanism of PCBP1 in regulating the process of PD models.…”
Section: Introductionmentioning
confidence: 99%
“…PCBP-1 plays an important role in the regulation of transcription and RNA metabolism at various levels ( Geuens et al, 2017 ). The previous studies have also indicated that PCBP-1 regulates the circadian clock ( Wu et al, 2021 ) as well as maintains the iron homeostasis ( Yanatori et al, 2020 ). Furthermore, abnormal nuclear distribution of PCBP-1 participates in Huntington’s disease (HD) pathogenesis, suggesting that as RBPs, like PCBP-1, may contribute to the pathophysiological processes under neurodegenerative conditions ( Geuens et al, 2017 ; Mori et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%